Where the Money Goes Understanding Litigant Expenditures for Producing Electronic Discovery - Pace, Nicholas M. (RAND Corporation, 2012)
This monograph provides a richly detailed account of the resources required by a diverse set of very large companies operating in different industries to comply with what they described as typical electronic-discovery requests and suggests ways to reduce those costs, as well as address concerns about duties to preserve data in anticipation of litigation.